2009
DOI: 10.1152/ajpheart.01108.2008
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide attenuates the expression of natriuretic peptide receptor C and associated adenylyl cyclase signaling in aortic vascular smooth muscle cells: role of MAPK

Abstract: Arejian M, Li Y, Anand-Srivastava MB. Nitric oxide attenuates the expression of natriuretic peptide receptor C and associated adenylyl cyclase signaling in aortic vascular smooth muscle cells: role of MAPK. Am J Physiol Heart Circ Physiol 296: H1859 -H1867, 2009. First published February 27, 2009 doi:10.1152/ajpheart.01108.2008We have earlier shown that the treatment of A10 vascular smooth muscle cells with S-nitroso-N-acetyl-penicillamine (SNAP); nitric oxide donor (NO) for 24 h decreased the expression of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 50 publications
(72 reference statements)
4
14
0
Order By: Relevance
“…As reported earlier [34, 38], the phosphorylation of ERK1/2 was significantly augmented by about 40% in VSMC from SHR compared with WKY and SNAP treatment attenuated the enhanced phosphorylation of ERK1/2 to control levels. In addition, this treatment also attenuated the ERK1/2 phosphorylation by about 25% in VSMC from WKY rats.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…As reported earlier [34, 38], the phosphorylation of ERK1/2 was significantly augmented by about 40% in VSMC from SHR compared with WKY and SNAP treatment attenuated the enhanced phosphorylation of ERK1/2 to control levels. In addition, this treatment also attenuated the ERK1/2 phosphorylation by about 25% in VSMC from WKY rats.…”
Section: Resultssupporting
confidence: 84%
“…In addition, NO has been shown to regulate MAPK activity [38, 48, 49]. To investigate the role of MAP kinase in SNAP-induced attenuation of enhanced expression of Giα proteins in VSMC from SHR, we inhibited MAP kinase activity by pretreating the cells with PD98059, a MEK inhibitor and then examined the effect of inhibition of MAP kinase on SNAP- induced decreased expression of Giα protein in VSMC from SHR and WKY rats.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell lysates were centrifuged at 12,000 rpm for 5 min at 4°C, and the supernatants were used for Western blot analysis. Cell viability was checked with the trypan blue exclusion technique and indicated that Ͼ90 ϳ 95% cells were viable, like described previously (4).…”
Section: Methodsmentioning
confidence: 99%
“…2A and 2B ) [76]. Since SNAP raises intracellular cGMP levels via sGC in A10 VSMC [65,66], additional studies demonstrated that 8-Br-cGMP (8-bromoguanosine 3’, 5’-cyclic monophosphate), a non-hydro-lyzable analogue of cGMP, mimicked the effect of SNAP and SNP and inhibited ET-1 stimulated ERK1/2 phosphorylation (Fig. 2C ) [76].…”
Section: No Modulation On Et-1 Signalingmentioning
confidence: 99%